Burnout among Nurses during Coronavirus Disease 2019 Outbreak in Shiraz - Kamali, Mahsa; Kalateh Sadati, Ahmad; Khademi, Mohammad Reza; Ghahramani, Sulmaz; Zarei, Leila; Ghaemi, Seyede Zahra; Tabirazi, Reza; Akbari, Maryam; Shokrpour, Nasrin; Mani, Arash; Heydari, Seyed Taghi; Lankarani, Kamran B (Galen Medical Journal, 2020)
Background: The function of healthcare workers, particularly nursing staff, in taking care of coronavirus disease 2019 (COVID-19) patients, cannot be overemphasized. As the pandemic lasts, burnout among the nursing staff needs to be considered as an important challenge. This was aimed to assess the nurses’ burnout and factors affecting this variable. Materials and Methods: In this cross-sectional study, Maslach Burnout Inventory was completed by 261 nurses in Shiraz hospitals (Iran) in April 2020. This questionnaire addresses different aspects, including emotional exhaustion, personal achievement, and depersonalization, to determine the intensity of perceived burnout among nurses during the outbreak. Results: Our data demonstrated that the nurses’ burnout in Shiraz hospitals during the COVID-19 pandemic was high (64.6%). Emotional exhaustion and depersonalization were observed in 63.6 and 53.3 percent of the participants, respectively. Moreover, the rate of successful personal achievement among these nurses was >97%. Work experience <10 years (P=0.016), hospital ward (P=0.044), the number of deaths observed by nurses during the COVID-19 pandemic (P<0.001), and the total number of shifts during the COVID-19 pandemic (P=0.006) had a positive correlation with emotional exhaustion. Conclusion: Workload and stress resulting from the COVID-19 outbreak seem to be one of the major causes of emotional exhaustion in nurses. The emotional exhaustion among nurses must be considered in epidemics, such as COVID-19. [GMJ.2020;9:e1956]